Effect of CAD/CAM abutment height and cement type on the retention of zirconia crowns - Silva, Camila Perfeito Evangelista da (2018)
Aim: To evaluate the effect of different Ti-base abutment heights and cement type on the pullout retention of zirconia-based restorations. Methods: Identical crowns were designed in a CAD software to fit two different Tibase abutment heights, as follows (n=10/group): (i) 4-mm-height Ti-base abutment (Tall), and (ii) 2.5-mm-height Ti-base abutment (Short). Four cement types were selected: (i) Temporary cement (Provisional); (ii) Glass-ionomer cement (Meron); (iii) self-adhesive resin cement (U200), and (iv) conventional resin cement (Ultimate) with universal adhesive for treatment of titanium and zirconia substrates. Pull-out testing was performed in a universal testing machine. Data were statistically evaluated through two-way analysis of variance following post-hoc comparisons by Tukey test. Results: Tall Ti-base abutments demonstrated similar retention to short abutments when data is collapsed over cement (p>0.74). Data evaluation as a function of cement type demonstrated the superiority of resin-based cements relative to provisional and glass-ionomer groups (p<0.01). Retentiveness data as a function of both factors demonstrated similar force to dislodgment between tall and short abutments for all within cement comparisons (p>0.42), except for U200 (p=0.032). Also, tall abutments cemented with Ultimate evidenced higher pull out values than U200 (p=0.043), and both were significantly more retentive than tall provisional and meron (p<0.001). No significant difference was observed between U200 and Ultimate cements for short abutments (p=0.758), and both presented statistically higher pullout values than provisional and glass-ionomer (p=0.001). Conclusions: While Ti-base abutment height have not influenced zirconia superstructure retentiveness, resin-based cements significantly evidenced higher retention than glass ionomer and temporary cements.